Evaluation of “Steroid-Sparing” Effects of Xanthena® Cream in Patients with Mild to Moderate Atopic Dermatitis - N. Cassano; A. Amoruso; S. Masci; S. De Paola; S. Salvatori; C. P. Agnusdei; S. Calabretta; A. Callea; F. Cellini; S. Centofanti; M. Cuomo; S. Curia; et al. (European Journal of Inflammation, 2003)
Emollients play an important role in the management of atopic dermatitis (AD). The aim of this study was to evaluate the efficacy and the “steroid-sparing” activity of an emollient cream (Xanthena® cream) in patients with mild to moderate AD. Patients were asked to apply twice a day for 7 days a cream containing hydrocortisone butyrate on the lesionai skin and then to apply Xanthena® cream only on the left side of affected areas. During the 2-month study period, the use of the corticosteroid cream was resumed in case of flare-up in any side. The results obtained show significant differences of both the total severity score and the intensity of each symptom and sign of AD between the skin areas treated with Xanthena® cream and the control areas (P<0.05); a relevant reduction of steroid requirement was also noted in correlation with the use of this emollient cream (P<0.05). A significant improvement was observed even after the first month of therapy for most symptoms, except for excoriations/fissuring, oozing/crusting and burning which improved only at 2 months. Treatment was well-tolerated by the majority of patients; adverse local reactions, mostly transient and of mild intensity, were observed in 7% of cases.